Guia de músicas para abordagens dos Temas Contemporâneos Transversais (TCTs) no ensino fundamental II - Oliveira, Jean Victor de (2021)
approach in basic education. Based on this premise, we produced a guide to popular songs on a digital platform, containing 111 works, distributed in different Brazilian musical genres. The electronic guide, available at the following electronic link: <https://www.sites.google.com/view/guiademusicastcts>, contains the following access categories: home, orientations, contemporary transversal themes, contemporary transversal subthemes, song title, and musical genre. The product was evaluated by 41 teachers distributed in the nine disciplines of elementary school II from a questionnaire formulated using google forms. In this qualitative research, the results showed that teachers appreciate the use of musicin the classroom, that they had contact with it since they were elementary school students, and they even suggested songs for the guide. Although the search and analysis of these works have been exhausting, the satisfaction is twofold: a personal and professional change in the relationship with music as a didactic resource; the perception that teachers believe that the guide has the possibility of contributing to the teaching of CTTs (TCTs).